Incompetent Plea Bargaining and Extrajudicial Reforms - Bibas, Stephanos (2012)
Last year, in Lafler v. Cooper and Missouri v. Frye, a five-to-four majority of the Supreme Court held that incompetent lawyering that causes a defendant to reject a plea offer can constitute deficient performance, and the resulting loss of a favorable plea bargain can constitute cognizable prejudice, under the Sixth Amendment. This commentary, published as part of the Harvard Law Review’s Supreme Court issue, analyzes both decisions. The majority and dissenting opinions almost talked past each other, reaching starkly different conclusions because they started from opposing premises: contemporary and pragmatic versus historical and formalist. Belatedly, the Court noticed that “ours ‘is for the most part a system of pleas, not a system of trials.’” Now the big question is which institutions can and will ameliorate poor defense lawyering retrospectively or prospectively. The upshot, I predict, will depend on semiprivate ordering: few reversals in court, but much more prospective extrajudicial reform. Lafler and Frye will not cause courts of appeals to invalidate many convictions for constitutional error. Courts are poorly equipped to remedy poor lawyers, particularly as plea bargaining creates little record and judges are reluctant to reverse final judgments. Moreover, judges cannot fix the massive underfunding and overwork that plague indigent defense counsel. But Lafler and Frye will probably have much bigger effects indirectly, in prompting solutions beyond the courts. Plea bargaining’s semiprivatized justice is best suited to semiprivatized remedies and reforms, backstopped by judges but driven by other actors. Other actors have the incentives and power to achieve, prospectively and flexibly, much that after-the-fact judicial review cannot. In the real world of plea bargaining, the parties’ stances are no longer antagonistic. Counterintuitively, even prosecutors and defendants have strong incentives to collaborate in explaining, promoting, and bulletproofing plea bargains